Description of three new species of Bopyrissa Nierstrasz & Brender à Brandis, 1931 (Epicaridea: Bopyridae) from Oceania with a key to species in the genus - An, Jianmei; Gong, Ling; Paulay, Gustav (Zootaxa, 2018)
Three new species in the parasitic isopod genus Bopyrissa Nierstrasz & Brender à Brandis, 1931, recorded from Kiribati, the Mariana Islands and French Polynesia, are described. These three species, B. distorta sp. nov., B. guamensis sp. nov. and B. oceania sp. nov., are the first species of the genus recorded from Oceania, occurring on three different hermit crab host species of genus Calcinus. The diversity of the genus is therefore increased to ten species. Bopyrissa distorta sp. nov. can be distinguished from congeners by the markedly distorted sinistral body of females and fused pleon of males. Bopyrissa guamensis sp. nov. differs from other dextral species of Bopyrissa in having a strikingly tuberculated edge to the pleomeres of females. Bopyrissa oceania sp. nov. differs from related species in that females possess eyes and that the barbula has smooth falcate projections on each side. A key to the ten species of Bopyrissa is presented, together with a tabular summary of their known geographic and host ranges.